Removal of Copper and Lead From Aqueous Solution by Tartaric Acid Modified Rice Husk - Wong, Koi Kim (2001)
The potential of rice husk (RH) modified with various carboxylic acids to remove Cu(n) from aqueous solution was investigated. It was found that the sorption capacity of rice husk was enhanced by this modification. Tartaric acid modified rice husk (TARH) has the highest sorption capacity for Cu(II). TARH was produced by treating RH with 1.2 M tartaric acid and heated at 180°C for 10 minutes. In order to understand the sorption characteristics of Cu(II) and Pb(II) by TARH, batch and column studies were performed under various experimental conditions. The parameters studied were pH, temperature, contact time, initial concentration of metal solutions, presence of competitive cations and chelators, sorbent dosage, rate of agitation, particle size of sorbent, bed height, flow rate and sorption-desorption cycles using synthetic solution and semiconductor electroplating wastewater. The results of batch studies indicated that the sorption process was pH dependent and exothermic. Kinetic study showed that uptake of Cu(II) and Pb(II) reached equilibrium after 60 minutes. The maximum binding capacities of the TARH at room temperature determined from the Langmuir isotherms were 31.85 and 120.48 mg/g for Cu(II) and Pb(II), respectively. In the presence of competitive cations and chelators, metal uptake decreased. The affinity of TARH for Pb(II) was greater than Cu(II) on a weight basis. The uptake increased with increasing sorbent dosage and agitation rate. The results of column studies showed that the utilised capacities of TARH at different bed depths agreed closely with the maximum sorption capacities obtained from Langmuir isotherm for both Cu(II) and Pb(II). The results also showed that breakthrough depended on bed depth, initial influent concentration of metal ion and flow rate. However, the effect of flow rate on sorption was minimal. The relationship between service time and bed depth was linear. Predicted breakthrough curves obtained from a two parameter mathematical model for Cu(II) and Pb(II) in wastewater agreed well with experimental values. In sorption-desorption study, Cu(II) and Pb(II) could be removed almost quantitatively by eluting with a 0.1M HCI solution and the column could be used repeatedly for at least 5 cycles in the treatment of wastewater.